Online Learning from Home with Cisco Webex - Soelis Setyoningrum (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
This article aims to evaluate the use of online learning application named Cisco Webex. Cisco Webex allows users to meet online, collaborate, and share content. Cisco Webex provides a breakthrough in disseminating home learning using Webex meetings. The home learning approach can certainly cause students to miss the opportunity to understand the subject matter more deeply the subject matter and not all parents have the ability to provide understanding for their children. To overcome this problem, schools utilizesmany online learning methods and one of it is Cisco Webex application which is intended to facilitate the students to learn at home during this pandemic outbreak. Keyword: learning from home, online learning, Cisco Webex Abstrak Artikel ini bertujuan untuk mengevaluasi penggunaan rumah belajar secara daring dengan Cisco Webex sebagai pembelajaran daring Cisco Webex memungkinkan pengguna untuk bertemu secara daring, berkolaborasi dan berbagi konten. Cisco Webex memberikan terobosan di dalam menyebarluaskan Rumah Belajar dengan menggunakan Webex Meetings. Pendekatan pembelajaran di rumah pastinya dapat menyebabkan siswa kehilangan kesempatan untuk memahami dan mengerti dengan lebih dalam materi pelajaran yang diberikan dan tidak semua orang tua punya kemampuan untuk memberikan pemahaman kepada putra atau putrinya. Untuk mengatasi hal tersebut, sekolah kami memanfaatkan banyak cara pembelajaran daring melalui aplikasi Cisco Webex agar dapat memfasilitasi semua siswa untuk tetap dapat belajar di rumah, aman, nyaman, dan tentram. Kata kunci: belajar dari rumah, pembelajaran daring, Cisco Webex